Integration of the All-in-One electrode in an electrochemical flow cell for in situ hydrogen peroxide supply in hydroxylation mediated by immobilized unspecific peroxygenase - Giovanni V. Sayoga; Victoria S. Bueschler; Hubert Beisch; Bodo Fiedler; Daniel Ohde; Andreas Liese (Electrochemistry Communications, 2025)
Hydrogen peroxide (H₂O₂) is a strong oxidizing agent that is commonly employed in chemical synthesis. Nevertheless, its utilization as a cosubstrate in biocatalytic reactions remains limited due to the deactivating effect on biocatalysts at an elevated concentration. An electrochemical synthesis of H₂O₂ represents an attractive approach, offering a controllable in situ generation of H₂O₂ without producing complex by-products. The objective of this study is to demonstrate the feasibility of the in situ electrogeneration of H₂O₂ using the All-in-One (AiO) electrode within a flow reactor technology. Integrating a bioelectrochemical system (BES) into a flow reactor technology, such as a flow cell, presents an alternative strategy for scale-up. In this study, the in situ generation of H₂O₂ is coupled with the hydroxylation of 4-ethylbenzoic acid catalyzed by the immobilized recombinant unspecific peroxygenase from Agrocybe aegerita (rAaeUPO) within a complete BES under batch and fed-batch operation modes. The electrochemical flow cell facilitates a controllable H₂O₂ generation by adjusting experimental parameters such as current density, aeration rate and residence time. The flow cell BES equipped with the AiO electrode yielded a catalytic productivity as high as 1.24 ± 0.02 mM h−1 (4.95 ± 0.1 g L−1 d−1), a total turnover number of rAaeUPO up to 3.38 · 105 ± 702 mol mol−1 and a turnover frequency up to 8.34 ± 0.14 s−1.